A study of goat and sheep production on the Masai group ranch at Elangata Wuas, Kajiado District - Wilson, R.T.; Peacock, C.P.; Sayers, A.R. (International Livestock Centre for Africa, 1981)
Presents results of an initial survey on sheep & goat production on the Masai group ranch at Elangata Wuas, Kajiado District in Kenya, describing population structure, animal morphology & production characteristics, with particular reference to age at first parturition, intervals between successive births, litter size, animal reproduction rate, growth, weight and viability; establishes a series of production indices using these traits. Analyzes effects of sex, parity, birth type, season & flock on all production characteristics and includes survey of management practices.